2020
DOI: 10.2147/ott.s244550
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ropivacaine Inhibits the Growth, Migration and Invasion of Gastric Cancer Through Attenuation of WEE1 and PI3K/AKT Signaling via miR-520a-3p</p>

Abstract: Background: Metastasis remains one of the greatest challenges involved in treating gastric cancer (GC). Ropivacaine (Rop) is not only a well-documented local anesthetic medicament but also has been reported to exert an antitumor role in cancer development. This study explored the effects of ropivacaine on the growth, migration and invasion of gastric cancer and the underlying mechanisms. Methods: Cell Counting Kit-8 (CCK8) assay was conducted to test the effect of Rop on the proliferation of AGS and BGC-823 GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…In previous studies, the PI3K/AKT pathway was reported as a major signaling pathway associated with tumor progression and invasion. 31,32 Therefore, we then examined the expression of PI3K/AKT-signaling-related molecules. The expression of p-AKT, and p-PI3K was lower in NCI-N87 with USP8 inhibitor group in Figure 5B.…”
Section: Usp8 Inhibitor Was Involved In Pi3k/akt Signaling Pathway Inmentioning
confidence: 99%
“…In previous studies, the PI3K/AKT pathway was reported as a major signaling pathway associated with tumor progression and invasion. 31,32 Therefore, we then examined the expression of PI3K/AKT-signaling-related molecules. The expression of p-AKT, and p-PI3K was lower in NCI-N87 with USP8 inhibitor group in Figure 5B.…”
Section: Usp8 Inhibitor Was Involved In Pi3k/akt Signaling Pathway Inmentioning
confidence: 99%
“…There have been many studies inhibition of PI3K/AKT signaling pathway of ropivacaine in vivo and in vitro [15][16][17]. Meanwhile, activation of the PI3K/Akt/mTOR signaling pathway has been con rmed to be closely related to the proliferation and migration of human keratinocytes [18][19][20].…”
Section: Ropivacaine Inhibited the Activation Of Pi3k/akt/mtor Pathway In Hacat Cellsmentioning
confidence: 99%
“…PI3K/Akt/mTOR pathway plays a crucial role in the proliferation, migration, metabolism and apoptosis of various cells [12][13][14]. Recent experimental studies have shown that ropivacaine decreased growth, migration and invasion of gastric cancer cells by inactivating the PI3K/Akt/mTOR signaling pathway [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-340, miR-379, miR-520a-3p, and miR-1254 inhibit the PI3K/AKT/mTOR signaling pathway by suppressing the direct targets SPP1, FAK, WEE1, and SMURF1. It is reported that an increase in the expression levels of miR-379, 520a-3p, 1254, and miR-340 resulted in a decrease in AKT phosphorylation [67][68][69][70] The other microRNAs directly interact with the main components of the PI3K/AKT/mTOR pathway. PI3K is acted upon by miR-142-5p, miR-216, and miR-491, inhibiting this pathway.…”
Section: Micrornas Associated With Gc Metastasis and Signaling Pathwamentioning
confidence: 99%